7-Benzenesulfonamido-3-methyl-8-oxo-5-thia-1-azabicyclo[4.2.0]octa-2-ene-2-carboxylic acid monohydrate - Shahzad Sharif; Mehmet Akkurt; Islam Ullah Khan; Manan Ayub Salariya; Sarfraz Ahmad (Acta Crystallographica Section E, 2010)
In the title compound, C14H14N2O5S2·H2O, the six-membered ring fused to the β-lactam unit has a twisted conformation. Weak intramolecular N—H...S and C—H...O interactions occur. Intermolecular C—H...S, N—H...O, C—H...O and O—H...O hydrogen-bonding interactions stabilize the crystal structure, forming a three-dimensional network. Weak C—H...π interactions are also present.